Anesthesia management of an aged patient with giant abdominal tumor and large hiatal hernia: A case report and literature review - Xiang, Bingbing; Yi, Mingliang; Yin, Hong; Chen, Rui; Yuan, Feng (Frontiers in Surgery, 2022)
Introduction: A giant abdominal tumor with a large hiatal hernia remains a rare disease with few studies regarding its implications in anesthesia. A large hiatal hernia may compress the heart and cause arrhythmia and even cardiac arrest, which greatly increases the risks and challenges of anesthesia management. Case description: We present a case in which a patient with a giant abdominal desmoid tumor and large hiatal hernia experienced a critical situation during anesthesia and surgery. Conclusions: It is a great challenge for anesthesiologists to manage a patient’s respiratory system and circulation. Careful perioperative management and optimized multidisciplinary teams are the key factors in the successful management of this rare condition. In addition, awake endotracheal intubation, ventilation preserving spontaneous breathing and target-directed fluid therapy play an essential role in anesthesia management.